Rhamphoriopsis hyalospora sp. nov. associated with decaying wood from China - Lin, Chuan-Gen; Liu, Jian-Kui; Chukeatirote, Ekachai; Hyde, Kevin D. (Phytotaxa, 2023)
Rhamphoriopsis hyalospora sp. nov., is described, illustrated and compared with other Rhamphoriopsis species. Evidence for the new species is provided by morphological comparison and molecular data analyses. Rhamphoriopsis hyalospora can be distinguished from other Rhamphoriopsis species by its caespitose conidiophores closely packed together but not forming synnemata, and aseptate, hyaline, ellipsoidal to obovoid, aguttulate conidia.